The Effectiveness of Entrepreneurship Education and Digital Literacy on Online Business Success with Entrepreneurial Mindset as A Moderating Variable (Study at Madrasah Aliyah in Mojokerto District) - Ria Indra Novita; Ludi Wishnu Wardana; Agus Sumanto (PT FORMOSA CENDEKIA GLOBAL, 2023)
Digital literacy is the ability to read, write and save digital text/content in digital format. Digitalization involves many changes and affects entrepreneurs and businesses. This study uses several methods using partial least squares linear regression (PLS-SEM) to estimate and confirm the given hypotheses. This study used Google Forms to collect data on Madrasah Aliyah students in Mojokerto regency. The respondents to this study are 356 respondents from three schools targeted for the study. The results show that digital culture cannot explain the success of online businesses. However, the study of entrepreneurship can explain how to do business and how to do business online. Furthermore, if business training and digital literacy support entrepreneurship as a medium, it will have a greater impact on online commerce.